POLA PENYEBARAN, KELIMPAHAN DAN ASOSIASI BAMBU PADA KOMUNITAS TUMBUHAN DI TAMAN WISATA ALAM GUNUNG BAUNG JAWA TIMUR [Distribution Pattern, Association and Abundance of Bamboo in Plants Community in Mount Baung Natural Tourism Park East Java] - Sofiah, Siti; Setiadi, Dede; Widyatmoko, Didik (Research Center for Biology-Indonesian Institute of Sciences, 2013)
One of bamboo forests which are located in a conservation area in Indonesia is Mount Baung Natural Tourism Park, East Java. Bambooforest is a uniqueness/distinctiveness in this area. Study of bamboo ecology in Mount Baung Natural Tourism Park was very important inconservation purposes. The objectives of the research were to assess the distribution pattern, association and abundance of bamboo species at Mount Baung Natural Tourism Park. A systematic quadrat method was used in this study. The distribution pattern of bamboo was calculated using Morisita Index by calculating the Chi-square formula while plant association was calculated using the contingency table. The results indicated that: (1) there were 11 plant species (bearing the Importance Value Index >10%) associated with bamboo, and showing a clumped distribution pattern, (2) bamboo supported the highest importance value, in which Bambusa blumeana was the dominant. The population structure of bamboo in this area showed pre-reproductive phase, indicating the dominance of young stage (D clump < 5m).